2004
DOI: 10.1002/elps.200305786
|View full text |Cite
|
Sign up to set email alerts
|

Determination of dissociation constants by competitive binding in partial filling capillary electrophoresis

Abstract: The determination of dissociation constands (K(d)) by competitive ligand binding in partial filling capillary electrophoresis is demonstrated. Two different strategies were applied, one of which only uses a single reporter ligand and a more elaborated one which suppresses systemic disturbances by using a racemic mixture as reporter. The dissociation constants obtained by both alternatives were virtually identical and in good agreement with those previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Competitive binding methods with a second substrate or ligand have been reported 20, 22, 62, 80–82 for systems that have small or no system‐response shifts for the substrate and complex.…”
Section: Ce‐based Methodsmentioning
confidence: 99%
“…Competitive binding methods with a second substrate or ligand have been reported 20, 22, 62, 80–82 for systems that have small or no system‐response shifts for the substrate and complex.…”
Section: Ce‐based Methodsmentioning
confidence: 99%
“…The displacement studies were performed by using several methods, including ultrafiltration [10], ED [11], crystallographic studies [12], CD [13], fluorescence spectroscopy [14,15], molecular modeling [16], highperformance affinity chromatography [17], and capillary electrophoresis (CE) in different modes including affinity CE, vacancy affinity CE, partial filling CE, near-infrared dye-displacement CE or CE-FA [1,[18][19][20][21]. Despite the fact that CE-FA method is widely used for binding parameters determination only a few research groups reported about its applicability for displacement studies [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The added volume of ␣-Me-Man in each step was in the same range as the evaporation during the separation so the volume and concentration of Con A was constant in the experimental series. The separation of the two AGP peaks ( t) was plotted versus the concentration of the inhibitor ␣-Me-Man [I] in the experiment and the dissociation constant (K D ) between Con A and inhibitor ␣-Me-Man was estimated from the nonlinear regression curve fit according to Nilsson et al [25] using the equation…”
Section: Con a Ace Inhibition Experiment; ␣-Me-man Added To Con Amentioning
confidence: 99%
“…Affinity constants are possible to estimate from the change in migration time when the absolute amounts of the affinity ligand is varied [24]. The affinity separation can also be used as a reporter system for the estimation of K A between the affinity ligand and other substances, competing for the same binding site [25].…”
Section: Introductionmentioning
confidence: 99%